Family Income, Mother’s Education and Number of Siblings with Toddler Growth and Development - Yuhanah Yuhanah; Grace Tedy Tulak (Universitas Aisyah Pringsewu, 2022)
The toddler age is a golden period in the cycle of human growth and development. At this time there is a rapid development of the brain and intelligence of children. The role of parents in stimulating the growth and development of children in this period is very important to prevent developmental delays. This study aims to analyze the relationship between family income, maternal education and the number of siblings with the growth and development of children under five. The research was conducted at the Posyandu in the working area of the Wundulako Health Center in March 2021. The sample in this study amounted to 207 mothers of children under five who visited the posyandu at the time of the study. The data was collected primarily by using a questionnaire and then analyzed by univariate and bivariate. The results showed a significant relationship between family income and toddler growth and development (p = 0.014). Maternal education did not have a significant relationship with growth and development (p = 0.173) and the number of siblings also did not have a significant relationship with child development (p = 0.299). The results of this research are expected to provide input to the health center regarding the growth and development of children under five in their working area. It is better if cadres actively screen the growth and development of children under five every month so that the growth and development of toddlers do not experience delays. Abstrak: Usia balita merupakan periode emas dalam siklus pertumbuhan dan perkembangan manusia. Pada masa ini terjadi perkembangan yang pesat pada otak dan kecerdasan anak. Peran orang tua dalam menstimulasi pertumbuhan dan perkembangan anak pada periode ini sangat penting untuk mencegah timbulnya keterlambatan tumbuh kembang. Penelitian ini bertujuan untuk menganalisis hubungan antara pendapatan keluarga, pendidikan ibu dan jumlah saudara dengan tumbuh kembang balita. Penelitian dilaksanakan di posyandu wilayah kerja Puskesmas Wundulako pada bulan Maret 2021. Sampel pada penelitian ini berjumlah 207 ibu balita yang berkunjung ke posyandu pada waktu penelitian. pengumpulan data dilakukan secara primer dengan menggunakan kuesioner kemudia dianalisis secara univariate dan bivariat. Hasil penelitian memperlihatkan signifikansi hubungan antara pendapatan keluarga dengan tumbuh kembang balita (p=0.014). Pendidikan ibu tidak memiliki hubungan signofokan dengan tumbuh kembang (p=0.173) dan jumlah saudara juga tidak memiliki signifikansi hubungan dengan tumbuh kembang balita (p=0,299). Hasil penelitian ini diharapkan dapat memberikan masukan kepada pihak puskesmas mengenai pertumbuhan dan perkembangan balita di wilayah kerjanya. Sebaiknya kader secara aktif melakukan skrining tumbuh kembang balita setiap bulan agar pertumbuhan dan perkembangan balita tidak mengalami keterlambatan.